2006
DOI: 10.1016/j.febslet.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation suppresses FAP‐1 mRNA level in A549 cells via p53 activation

Abstract: Ionizing radiation (IR) is known to upregulate cell surface Fas through p53 activation in various cells. However, the signaling pathway intermediating between p53 activation and cell surface Fas upregulation remains to be elucidated. Recently, Fas-associated phosphatase-1 (FAP-1) has been reported to associate with Fas and inhibit cell surface Fas expression. We evaluated the expression of FAP-1 mRNA following IR in A549 cells. Ionizing radiation inhibited the expression of FAP-1 mRNA. Pretreatment with p53 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Consistent with these studies, we showed that knockdown of FAP-1 encouraged the cell surface display of Fas. Furthermore, the promoter of FAP-1 has been identified as a potential binding site for p53, and p53 activation suppresses the expression of FAP-1 (48,49). We found similar results in that the overexpression of p53 reduced the protein level of FAP-1.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with these studies, we showed that knockdown of FAP-1 encouraged the cell surface display of Fas. Furthermore, the promoter of FAP-1 has been identified as a potential binding site for p53, and p53 activation suppresses the expression of FAP-1 (48,49). We found similar results in that the overexpression of p53 reduced the protein level of FAP-1.…”
Section: Discussionsupporting
confidence: 77%
“…Fas mRNA and protein levels increased two-to fourfold after a respiratory syncytial virus infection (32). Fas was upregulated in response both to cigarette smoke extracts and to ionizing radiation (21,47). Inhibitors of epidermal growth factor receptor tyrosine kinase, such as gefitinib and ZD1839, and extracts of the Chinese herbs gossypol and casuarinin all upregulated Fas signaling and apoptosis (7,8,25,36).…”
mentioning
confidence: 99%
“…P53 mutations were associated with the development of multiple cancer types [22, 23]. The G72C single nucleotide polymorphism is located in the apoptosis-inducing region of the protein, and substitution of the G with a C nucleotide leads to an amino acid exchange from arginine to proline.…”
Section: Introductionmentioning
confidence: 99%